An efficient W-band InP DHBT digital power amplifier. Issue 6 (14th March 2017) - Wentzel, Andreas; Hossain, Maruf; Stoppel, Dimitri; Weimann, Nils; Krozer, Viktor; Heinrich, Wolfgang
Abstract : This paper presents for the first time high-efficiency W-band power amplifiers (PAs), the design of which follows the digital PA (DPA) design concept. Two DPAs with different output networks have been realized: a single-band version (S-DPA) for 95 GHz and a dual-band design (D-DPA) for signal frequencies fS of 68 GHz (first band) and 76 GHz (second band), respectively. The PAs are realized as monolithic microwave-integrated circuits (MMICs) in a 0.8 μm InP DHBT transferred-substrate process. They utilize a double-emitter-finger DHBT unit cell with an emitter area of 2 × 0.8 × 6 μm 3 each. In contrast to the usual W-band PAs, the proposed single-stage amplifier MMICs do not apply any special reactive matching for the transistor, which leads to very compact chip sizes of 0.27 mm 2 (S-DPA) and 0.39 mm 2 (D-DPA). The S-DPA includes one band-pass filter (BPF) at the output with 0.6 dB insertion loss (IL) and 24 dB input return loss (RL) at the signal frequency of 95 GHz. The dual-band BPF shows 0.7 dB IL in both bands with a RL of more than 21 dB each. Applying an overdriven sinusoidal input signal to emulate digital operation the DPAs achieve a maximum output power of 14.4 dBm and power-added efficiency of 31% when using the single-band configuration. Collector efficiencies of more than 80% and the flexible multi-band operation demonstrated prove the great potential of the digital PA concept for future high-speed communications.